Seasonal differences in the effects of local concentrations of atmospheric substances and meteorological elements on asthma exacerbation of children in metropolitan area, Korea: A 13-year retrospective single-center study - Hwang, Jae Kyoon; Na, Jae Yoon; Lee, Kyung Suk; Oh, Jae-Won; Choi, Young-Jin (Frontiers in Pediatrics, 2023)
Purpose Air pollutants contribute to asthma exacerbation, and the types of air pollutants involved in acute asthma exacerbation may differ depending on climate and environmental conditions. This study aimed to identify factors affecting asthma exacerbation in each of the four seasons so that to prevent acute asthma exacerbation and to establish effective treatment strategies for each season. Methods Pediatric patients aged 0–18 years old hospitalized or admitted to the emergency room for asthma exacerbation at Hanyang University Guri Hospital between January 1, 2007, and December 31, 2019 were recruited. The number of asthma exacerbations comprised the total number of patients admitted to the emergency room or hospitalized for asthma and treated with systemic steroids. The association between the number of asthma exacerbations/week and average concentrations of atmospheric substances and meteorological elements in that week were analyzed. Multiple linear regression analyses were performed to examine the association between various atmospheric variables and the number of asthma exacerbations. Results The number of asthma exacerbations was found to be associated with the concentration of particulate matter with an aerodynamic diameter of ≤10 μm in that week in autumn. No atmospheric variables exhibited an association in other seasons. Conclusions Air pollutants and meteorological factors affecting asthma exacerbation vary by season. Moreover, their effects may change via their interaction with each other. The results of this study suggest that it will be helpful to establish differentiated measures for each season to prevent asthma exacerbation.